2018
DOI: 10.7717/peerj.5740
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and factors affecting length of hospital stay for children and adults with burns in Zunyi, China: a retrospective study

Abstract: ObjectiveBurn wounds are a global public health problem, and a large number of casualties are caused by burns each year. In this study, we explored the epidemiological characteristics associated with burns and the factors affecting the length of hospital stay (LOS) in children and adults with burn wounds.MethodsRecords of patients with burns in the Affiliated Hospital of Zunyi Medical University from January 1, 2014 to August 31, 2016 were retrieved. Information on demographic characteristics, mechanism of bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
3
7
1
3
Order By: Relevance
“…skin grafting, in Australian children from rural locations as compared to metropolitan areas (Hyland et al 2015). We found that split skin grafts increased LOS for Aboriginal and Torres Strait Islander children in this study, which is different to past research in other populations, which reported grafting as decreasing LOS in children (Wang et al 2018). Recent research has suggested that Aboriginal and Torres Strait Islander children are remaining longer in hospital for their burns treatment, due to perceived social issues from clinical teams and for easier access to multidisciplinary support and care i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…skin grafting, in Australian children from rural locations as compared to metropolitan areas (Hyland et al 2015). We found that split skin grafts increased LOS for Aboriginal and Torres Strait Islander children in this study, which is different to past research in other populations, which reported grafting as decreasing LOS in children (Wang et al 2018). Recent research has suggested that Aboriginal and Torres Strait Islander children are remaining longer in hospital for their burns treatment, due to perceived social issues from clinical teams and for easier access to multidisciplinary support and care i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…The most significant prognostic factor providing the highest discharge ratios in all children was %TBSA, similar to previous research (Dolp et al 2018;Möller et al 2017;Hussain and Dunn 2013;AbdelWahab et al 2018;Taylor et al 2017;Gravante et al 2007;Matin et al 2015;Elrod et al 2019;Wang et al 2018;Hyland et al 2015;Meshulam-Derazon et al 2006). In Aboriginal and Torres Strait Islander children, greater %TBSA levels have been reported to increase LOS, however our ratios were greater than previous reports (Möller et al 2017).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations